CONSUMPTION OF SOFT DRINKS IS ASSOCIATED WITH DIABETES MELLITUS IN TEENAGERS - Setyawan, Yuswanto (HEARTY, 2025)
Consumption of drinks containing high sugar causes diabetes mellitus. Diabetes causes insulin resistance, defined as where normal or increased insulin levels result in a weakened biological response. Classically, this refers to impaired sensitivity to insulin-mediated glucose disposal. Research with a cross-sectional model using adolescents as research subjects Regarding soft drinks. The population in this study were adolescents aged 12-24 years according to WHO criteria. The sample used in this study was 118 respondents. The sampling technique used quota sampling.  Soft drinks increase the incidence of diabetes mellitus compared to those who do not consume soft drinks, such as Tingling or numbness in the hands and feet, as many as 61.9% of teenager feel these symptoms. Furthermore, teenager also often feel wounds that do not heal as many as 59.3% and Constant fatigue as many as 57.6%. For further researchers, it is hoped that they will examine the eating patterns of adolescents associated with the consumption of carbonated drinks and diabetes mellitus.